Emeril! : - Turner, Marcia Layton (Wiley, 2004)
A revealing look at the real "Emeril live". Emeril Lagasse is a phenomenon-a television chef and restaurateur who has parlayed his outsized personality and gastronomic acumen into a multi-million-dollar culinary empire. Along the way, he's added new catchphrases to the American idiom-"bam," "kick it up a notch," and "pork fat rules"-and won the hearts (and stomachs) of millions of loyal fans. Now, for the first time, you get to enter into Emeril's incredible world. Filled with candid stories and vivid details, EMERIL! Inside the Amazing Success of Today's Most Popular Chef reveals how this culinary connoisseur made it to the top of his profession, while staying true to his main mission-showing ordinary people how to have fun with food. Weaving together Emeril's personal and professional journeys to international stardom, EMERIL! Inside the Amazing Success of Today's Most Popular Chef offers an entertaining look at how one of the world's most talented chefs became a household name.